The Influence of Wahhabi Teachings on Its Congregation in Indonesia: An Analysis of Religion as Social Action in Max Weber’s Perspective - Fiqi Restu Subekti (International Review of Social and Cultural Studies, 2025)
Wahhabi teachings originating from Saudi Arabia have grown rapidly in Indonesia and influenced the religious understanding and practices of its worshipers. This study analyses the phenomenon using Max Weber’s theory of religion as social action. In Weber’s perspective, religion not only functions as a belief system, but also influences the social action patterns of individuals and groups. This research uses a qualitative method with a literature study approach to explore how Wahhabi teachings shape the mindset and social behaviour of its followers. The results show that Wahhabi teachings tend to emphasise a more scripturalist and exclusive understanding of Islam, which has an impact on changes in social interaction in society. In addition, social actions carried out by Wahhabi worshipers are often based on absolute value orientation, as explained in Weber’s theory. This study provides insight into the role of religion in shaping social dynamics, especially in the context of Islamic diversity in Indonesia.